2020
DOI: 10.1002/ehf2.12707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canagliflozin in patients with type 2 diabetes and chronic heart failure: a randomized trial (CANDLE)

Abstract: Aims Little is known about the impact of sodium glucose co-transporter 2 (SGLT2) inhibitors on cardiac biomarkers, such as natriuretic peptides, in type 2 diabetes (T2D) patients with concomitant chronic heart failure (CHF). We compared the effect of canagliflozin with glimepiride, based on changes in N-terminal pro-brain natriuretic peptide (NT-proBNP), in that patient population. Methods and results Patients with T2D and stable CHF, randomized to receive canagliflozin 100 mg or glimepiride (startingdose: 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 25 publications
(42 reference statements)
3
78
0
Order By: Relevance
“…Those studies suggested that improved vascular function was likely to be associated with empagliflozin-mediated glycemic and non-glycemic actions, such as weight loss and volume contraction. This empagliflozin-induced reduction in ePV was comparable to that reported by previous studies of SGLT2 inhibitors 13,35 . However, a direct effect of the agent on vascular function remains to be fully elucidated.…”
Section: And Other Physiologicalsupporting
confidence: 90%
“…Those studies suggested that improved vascular function was likely to be associated with empagliflozin-mediated glycemic and non-glycemic actions, such as weight loss and volume contraction. This empagliflozin-induced reduction in ePV was comparable to that reported by previous studies of SGLT2 inhibitors 13,35 . However, a direct effect of the agent on vascular function remains to be fully elucidated.…”
Section: And Other Physiologicalsupporting
confidence: 90%
“…At baseline, the median trial mean glycated haemoglobin A1c was 8.1% and BMI was 30.1. Eligibility criteria included coronary artery disease or macrovascular disease in 35 trials, 3 6 7 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 atrial fibrillation in 1 trial, 65 heart failure in 9 trials, 66 67 68 69 70 71 72 73 74 chronic kidney disease and/or albuminuria in 37 trials, 8 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 RCTs [ 10 , 24 , 25 , 29 31 , 33 , 39 52 ] were recognized eligible in this meta-analysis, including 3 in crossover design [ 41 , 44 , 50 ]. A total of 10,978 participants were enrolled, including 6236 in the SGLT2i group and 4821 in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow-up period ranged from 14 days to one year, including three studies [ 41 , 50 , 51 ] less than 3 months. Participants with T2DM that were mostly in stage A–B HF were enrolled in 10 studies [ 24 , 25 , 39 , 40 , 44 , 46 , 48 , 49 , 51 , 52 ], and patients with T2DM and stage C HF were enrolled in 11 studies [ 10 , 29 31 , 33 , 41 – 43 , 45 , 47 , 50 ]. LVMI, LVEDVI, LVESVI, LAVI, LVEF, GLS, the E/e’ ratio, plasma NT-proBNP level, and the KCCQ score were reported in 6 [ 24 , 25 , 29 , 44 , 45 , 52 ], 3 [ 25 , 29 , 30 ], 3 [ 25 , 29 , 30 ], 4 [ 25 , 29 , 45 , 52 ], 9 [ 24 , 25 , 29 31 , 39 , 40 , 44 , 45 ], 4 [ 24 , 39 , 44 , 51 ], 8 [ 24 , 25 , 30 , 31 , 44 , 45 , 49 , 52 ], 11 [ 10 , 24 , 25 , 31 , 41 , 44 46 , 48 50 ] and 3 [ 10 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation